1995
DOI: 10.1016/s0022-5347(01)66670-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens in the Treatment of Prostate Cancer

Abstract: A 1 mg. dose of diethylstilbestrol remains a medial alternative to bilateral orchiectomy in the treatment of advanced prostate cancer. Doses of 3 mg. diethylstilbestrol or more have a prohibitively high risk of cardiovascular death. Further studies comparing the efficacy, complications and cost of regimens containing oral estrogens or parenteral estrogens with agents that increase efficacy (for example antiandrogens) and decrease toxicity (for example anticoagulants) to results of other regimens, such as combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(51 citation statements)
references
References 71 publications
2
46
0
2
Order By: Relevance
“…To date, no study of secondary hormonal treatment has shown a benefit in terms of survival, but most trials have been smaller and heavily confounded by future treatments used. In patients treated with monotherapy using luteinizing-hormone releasing-hormone agonist or in those who have had an orchiectomy, total androgen blockade with testosterone antagonists such as bicalutamide can offer psa responses in 30%-35% of patients 5,6 .…”
Section: Secondary Hormonal Manipulationsmentioning
confidence: 99%
“…To date, no study of secondary hormonal treatment has shown a benefit in terms of survival, but most trials have been smaller and heavily confounded by future treatments used. In patients treated with monotherapy using luteinizing-hormone releasing-hormone agonist or in those who have had an orchiectomy, total androgen blockade with testosterone antagonists such as bicalutamide can offer psa responses in 30%-35% of patients 5,6 .…”
Section: Secondary Hormonal Manipulationsmentioning
confidence: 99%
“…Several classes of drugs induce castrate levels of testosterone through suppression of LH release from the pituitary gland, including diethylstilbestrol (DES) 14 luteinizinghormone-releasing hormone (LHRH) agonists include goserelin, leuprolide and buserelin. 15,16 The¯are reaction can be prevented by cyproterone acetate or DES 1 week prior to the LHRH analog, or blocked by nonsteroidal anti-androgens like¯utamide or bicalutamide.…”
Section: Reversible Androgen Suppression Therapymentioning
confidence: 99%
“…Estrogen therapy or orchidectomy have been the standard treatments for advanced prostate cancer in the last four decades (Cox & Crawford 1995). However, the exact mechanism of estrogen action in the prostate is not yet completely understood.…”
Section: Introductionmentioning
confidence: 99%